Speech Encryption Technique Based on Bio-Chaotic Algorithm (Al-Mansour Journal, 2022)
In today world of advancement, it is mandatory task to share, distribute and exchange the information like image, speech, text files throw public wired/wireless networks. Therefore, security gains more and more importance especially in those organizations where information is more critical and more important. Instead of using the traditional encryption techniques, Biometrics like speech uniquely identifies a person and a secure method for stream cipher, because Biometric characteristics are ever living and unstable innature. In this paper wavelet packet transform used to decomposition each frame in the speech signal, then present anew algorithm used two steps: (1) addition of noise derived from three chaotic maps (Henon, Logistical, and Ikeda) to the decomposition signal. (2) Chosen bio-chaotic stream cipher which encrypted the speech signal to stored it into the databases to make it moresecure by using a biometric key and a bio-chaotic function. In this paper present how to generate the bio-chaotic key by using any chosen frame (each frame is that of 256 sample long) to make it the security key. Chaotic function is used to make the algorithm more secure and make the process of the encryption and decryption more complex. Experimental result of the algorithm shows that the algorithm is faster, stronger and more secure. Use the matlab version of eighth in the different treatments stage.
Keywords: Biometric; chaotic map; speech; wavelet packet transform; encryption